Digitizing AJN - &NA (AJN, American Journal of Nursing, 2006)
BACKGROUND: Urinary incontinence following laparoscopic radical prostatectomy is a prevalent and debilitating condition that significantly diminishes the quality of life of patients with prostate cancer. PURPOSE: This study aimed to elucidate the prevalence and determinants of post-prostatectomy urinary incontinence in patients with prostate cancer and to construct a risk prediction model for postoperative urinary incontinence. METHODS: We conducted a retrospective analysis of patients diagnosed with prostate cancer who underwent laparoscopic radical prostatectomy at our institution from January 2022 to August 2024. The study included comprehensive data collection and comparative analysis between patients who developed postoperative urinary incontinence and those who did not. RESULTS: A total of 310 patients were included in the study. The incidence of urinary incontinence following laparoscopic radical prostatectomy was 14.84%. Correlation analysis revealed that age (r = 0.631), body mass index (BMI) (r = 0.518), diabetes (r = 0.607), and duration of surgery (r = 0.662) were significantly associated with postoperative urinary incontinence. Logistic regression identified 70 years of age or older (odds ratio [OR], 1.996; 95% CI, 1.258-2.662), BMI of 24 or higher (OR, 2.057; 95% CI, 1.834-2.605), presence of diabetes (OR, 2.815; 95% CI, 2.031-3.169), and surgery duration of 60 minutes or more (OR, 2.931; 95% CI, 2.247-3.215) as independent predictors of postoperative urinary incontinence. The predictive model demonstrated an area under the receiver operating characteristic curve of 0.794 (95% CI, 0.768-0.845), indicating good discriminatory ability. CONCLUSION: Urinary incontinence following laparoscopic prostatectomy for prostate cancer is very common, particularly among patients with risk factors identified by this model. Close monitoring and timely intervention are crucial to mitigate the risk of developing postsurgical urinary incontinence.